Optimization of determination and application of complexly distributed loads on a double curvature cable-stayed covering - V. A. Dagaev; G. M. Purvin; F. S. Shkoliar (Vestnik MGSU)
Introduction. In recent years, the development of programming affects more and more spheres, including the architectural and construction field. New tools appear in the design activity allowing to describe numerically the parameters of building structures, with the help of whicиh it is easy to change their shape and configuration. This direction allows to get away from more labour-intensive and time-consuming processes of manual editing of graphic materials. This approach to architectural design is called parametric modelling. Without it, it is difficult to imagine the creation of complex geometric shapes of buildings, both multi-storey and large-span, to which cable-stayed coverings can be referred. The interest in such structures, due to their impressive shaping, has turned their design into a complex engineering and technical task and actual work.Materials and methods. The process of optimization of the collection of loads on curvilinear forms was more clearly demonstrated on the example of determination and application of snow and wind loads on the cable-stayed covering of double curvature of the velodrome building, as, according to normative documents, the geometry of the building depends on the transition coefficient from the weight of the snow cover of the ground to the snow load on the covering and the aerodynamic coefficient, which, as a rule, are determined by the results of blowing, but in order to reduce the labour intensity of the study, the distribution zones of these coefficients were interpolated according to the forms already available in normative documents.Results. A collection of loads on the computational finite element scheme of the velodrome building with a double curvature covering by an orthogonal cable-stayed network, including 4 types of snow load and 2 types of wind load, was performed.Conclusions. The use of Grasshopper made it possible to get away from simplification and interpolation of both the magnitude of pressure from snow and wind in several directions and the values of load areas at each point of the cable-stayed network. This more accurate approach together with the results of aerodynamic tests and automated data transfer to the calculation systems will allow to determine more accurately the SSS of complex coverings, to avoid recalculation and reassignment of complex non-uniformly distributed linear and nonlinear loads in the calculation schemes when changing the initial data with saving labour and time costs for the control of these processes.